Low complexity duty cycle modulation model predictive current control of permanent magnet synchronous motor - Deliang Yu; Chuanchang Zhang; Qingbo Guo; Minghao Zhou (IET Power Electronics, 2023)
Abstract This study proposes a model predictive current control algorithm for the synchronous permanent magnet motor with low complexity duty cycle modulation. Three single‐phase voltage vectors are simulated to synthesize the target voltage vector that enables the current to achieve deadbeat control. The algorithm can change the amplitude and direction of the synthesized vector and extend the selection range of the synthesized vector to the whole hexagonal region. That is to say, this method can realize the deadbeat control of the d‐axis and q‐axis currents, and reduce the current pulsation. Moreover, this method only needs one action time operation, which can directly convert the action time of the voltage vector into a three‐phase duty cycle after equivalent processing and over‐modulation of the action time of the voltage vector. It is not necessary to traverse multiple sectors for optimization, which simplifies the modulation method and reduces the computational complexity. The effectiveness and reliability of the proposed method are verified by theoretical derivation and experimental results.